ANALYSIS OF THE IMPLEMENTATION OF MEDICINE STORAGE SYSTEMS IN PHARMACIES - Ahmad Subagiyo; Niati Ambarsari, Milla Oktaviani (Adisam Publisher, 2025)
The pharmacy is one of the places and dedication of the pharmacist profession to carry out pharmaceutical work. Storage of medicines in pharmacies is an inseparable part of medicine management activities. The activity of storing and maintaining the medicines received in a safe place to maintain the quality of the medicines and from theft is medicine storage. One of the determining factors for the quality of distributed medicines is a good and appropriate medicine storage system. Drug storage is an inseparable part of all pharmaceutical activities, both hospital pharmacy and community pharmacy. The act of keeping received medications in a location that is both secure against theft and capable of preserving their quality is known as medicine storage. An appropriate and good storage system will be one of the determining factors for the quality of medicines distributed. Implementing a medicine storage system in pharmacies is very crucial to ensure that medicines are stored safely, efficiently and in accordance with regulatory standards. Implementing a good medicine storage system not only helps in maintaining the quality and effectiveness of medicines, but also increases the operational efficiency of pharmacies and ensures patient safety.